Effects of 3d-imi-vle on student nurses’ knowledge, performances, satisfaction and confidence: a mixed methods study - Khraisat, Adam Mahmoud Salameh (2021)
Virtual Learning Environments (VLE) is a platform that enables collaborative learning among the students who participate at times and places of their own choice through a computer network. Intramuscular injection (IMI) for the nursing students has been taught through the existing IMI teaching method, which has many faults according to the literature, and there is a need to use the available modern technology to support the teaching effectiveness. The current study aimed to develop, implement, and evaluate a VLE Learning Management System (LMS) named as the Online 3D-IMI-VLE and to evaluate the effectiveness of the Online 3D-IMI-VLE and the traditional IMI teaching method among nursing students. A mixed-methods design (Embedded Sequential) was conducted in two phases. Phase I, a quasi-experimental study, included a combination of OSCE and MCQ examination for both groups, and questionnaire data on students’ satisfaction and confidence after using the educational methods. In Phase I, 30 students from each university (USM and IIUM) were recruited following the inclusions criteria. The experimental group used the Online 3D-IMI-VLE teaching method, while the control group used the traditional or existing IMI teaching method. Phase II was a qualitative exploration of the student’s learning experiences about the study, in-depth, semi-structured interviews were employed. Interviews with selected participants were audio-recorded, and a written interview with all the students was transcribed fully and analysed thematically, assisted by the ATLAS.ti. The results of the Phase I showed that USM as the experimental group (mean = 78.20) significantly outscored IIUM (mean = 58.66) as the control group in OSCE findings by using checklists (p<0.001) and global rating (p<0.001). Meanwhile, in the MCQ scores, USM as an experimental group (median = 7.0, IQR = 5 in the pre pre-intervention and median = 12.5, IQR = 1 in the post-intervention) significantly outscored IIUM (median = 11.0, IQR = 2 in the pre-intervention and median = 11.0, IQR = 2 in the post-intervention) as the control group (p<0.001). There was a significant median difference of students’ confidence between the experimental (Median = 36.0) and the control group (Median = 32.0) with (p=0.024). Also, the End-User Computing Satisfaction score showed the students are highly satisfied (Median = 52) with the experimental LMS. While exploring further a significant correlation between the students’ confidence score (r = .376) and the OSCE checklist score (r = .359) with (p=0.003) and the global rating score (p=0.005), the findings of Phase II revealed that three themes emerged from the data: 1) Student’ overall satisfaction, 2) learning experience, 3) learning methodology. The current study minimizes the need for the physical presence among the students, physical sessions between students and nurse educators, and physical interaction of the students with the lab equipment. This study found that the Online 3D-IMI-VLE method can replace or added together to the traditional IMI teaching method both in theory and clinical settings. The finding of the current study is suggestive regarding a gradual adaptation of modified nursing curriculums, integration of 3D simulation to practice nursing skills and development of LMS.